Like Peeling an Onion: An Examination of Cultural Identity Among Adult Learners - Talmadge C. Guy; John W. Schell; Jennifer Burnside; Grace Thorton; Kenner Scott (Adult Education Research Conference, 1998)
This paper describes the results of a study concerning the cultural identity of adult learners in graduate programs at the University of Georgia. Employing analytic induction research design the research team, itself a culturally diverse group of graduate students and professors, analyzes focus group transcript data. The conclusion is reached that verbal statements aside, cultural identity is complex and manifested situationally. Adult educators are advised to adopt sophisticated tools to assess learner identity issues in order to challenge learners to think more critically about their assumptions and biases toward those who are culturally different.